Análisis de la participación de las MIPYMES en la contratación de obras de menor cuantía de obras en la Empresa Pública Metropolitana de Agua Potable y Saneamiento de Quito - Castro Blacio, Leonela Silvana (2018)
Ecuador is a country mostly established by small and medium companies, that is why it promotes their participation in the public procurement as its main objective. Specifically, the processes of constructions minor amount1, allows the participation of the popular and solidary economy members and those from small companies since it is the easiest public procurement for architects and civil engineers, in terms of amounts, specifications, time, equipment and staff for contracts. The present research focuses to analyze the participation of small companies and the popular and solidary economy actors, excluding the companies qualified as medians, in the processes of Constructions minor amount. This research developed its base awareness in the Public Metropolitan Enterprise for Water and Sewage – EPMNAPS – Agua de Quito, supported by current regulations and studied during the period 2013 to 2016.